Alternative service models for delivery of healthcare services in high-income countries: a scoping review of systematic reviews. Issue 1 (29th January 2019) - Jessup, Rebecca L; O'Connor, Denise A; Putrik, Polina; Rischin, Kobi; Nezon, Janet; Cyril, Sheila; Shepperd, Sasha; Buchbinder, Rachelle
Abstract : Introduction: Costs associated with the delivery of healthcare services are growing at an unsustainable rate. There is a need for health systems and healthcare providers to consider the economic impacts of the service models they deliver and to determine if alternative models may lead to improved efficiencies without compromising quality of care. The aim of this protocol is to describe a scoping review of the extent, range and nature of available synthesised research on alternative delivery arrangements for health systems relevant to high-income countries published in the last 5 years. Design: We will perform a scoping review of systematic reviews of trials and economic studies of alternative delivery arrangements for health systems relevant to high-income countries published on 'Pretty Darn Quick' (PDQ)-Evidence between 1 January 2012 and 20 September 2017. All English language systematic reviews will be included. The Cochrane Effective Practice and Organisation of Care taxonomy of health system interventions will be used to categorise delivery arrangements according to: how and when care is delivered, where care is provided and changes to the healthcare environment, who provides care and how the healthcare workforce is managed, co-ordination of care and management of care processes and information and communication technology systems. This work is part of a 5-year Partnership Centre for Health System Sustainability aiming to investigate and create interventions to improve health-system-performance sustainability. Ethics and dissemination: No primary data will be collected, so ethical approval is not required. The study findings will be published and presented at relevant conferences.